Creep rupture ductility of Gr.91 and Gr.92 at 550°C to 700°C. (3rd July 2020) - Abe, Fujio
ABSTRACT: The creep rupture ductility has been investigated for Gr.91 and Gr.92 at 550 to 700°C for up to 118, 648.8 h. The degradation in the reduction of area (RA) is more significant in Gr.92 than in Gr.91 at 550°C to 700°C. The boron nitride particles are responsible for the degradation in RA in Gr.92 at long times by accelerating the formation of creep voids. The creep ductility parameter λ decreases to small values below 5 for Gr.92 at long times at 650°C and 700°C, while that is larger than 5 for Gr.92 at 550°C and 600°C and for Gr.91 at 550°C to 700°C. The data exhibiting λ > 5 and λ < 5 in the λ versus time diagram correspond to the data in the necking and creep void dominant regions, respectively, in the RA versus total elongation diagram.